(untitled) (Jurnal Pembangunan Sosial, 2010)
Religion or religiosity in particular, has received less attention by competent social scientists. This is because, among other things, certain concepts in religion are difficult to define. The aim of this article is to examine the dimension of religiosity as understood by Islamic scholars. To achieve this objective, five Islamic scholars from Malaysia and one Islamic scholar from Egypt were selected through purposive sampling as key informants. Data obtained were analysed using descriptive analysis. All key informants agreed that dimension of aqidah, syariah and akhlak are the core dimension of Islamic religiosity.